2017
DOI: 10.5897/jssem2015.0540
|View full text |Cite
|
Sign up to set email alerts
|

Improving available phosphorus in acidic soil using biochar

Abstract: Understanding of phosphorus (P) retention and release mechanisms provides crucial information for the effective management of phosphorus to enhance crop production and sustain soil. In acidic soil, available phosphorus is fixed by aluminum and iron. To overcome this problem, soils are limed to fix aluminum and iron. But this practice is not economical for small scale farmers and also it is not environmentally friendly. This study was conducted to improve phosphorus availability using biochar produced from coff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This gradually neutralizes soil acidity and hence makes fixed phosphorus available in the soil solution. This result was in agreement with Bayu, et al [42] who reported increased soil available phosphorus with application of coffee husk biochar. Therefore, application of coffee husk compost to acid soil could increase available phosphorus contents of soil through releasing of phosphorus in it and also by increasing soil pH which reduces phosphorus fixation.…”
Section: Soil Available Phosphorussupporting
confidence: 93%
See 2 more Smart Citations
“…This gradually neutralizes soil acidity and hence makes fixed phosphorus available in the soil solution. This result was in agreement with Bayu, et al [42] who reported increased soil available phosphorus with application of coffee husk biochar. Therefore, application of coffee husk compost to acid soil could increase available phosphorus contents of soil through releasing of phosphorus in it and also by increasing soil pH which reduces phosphorus fixation.…”
Section: Soil Available Phosphorussupporting
confidence: 93%
“…In all the treatments except the control, soil pH progressively increased while the exchangeable acidity decreased with increased rates of coffee husk compost and lime. This corroborates with the findings of Taye et al [41], Kasongo, et al [20,22], Nduka, et al [23] and Bayu, et al [42]. It could be attributed to reduction of Al 3+ ions concentration in soil solution and in exchangeable sites because of lime and manure application [18].…”
Section: Effects Of Coffee Husk Compost and Lime Amendments On Soil Organic Carbon Total Nitrogen And Available Phosphorussupporting
confidence: 91%
See 1 more Smart Citation
“…The C content reached for the PL-BC (97,94 wt%) and the CH-BC (97,06 wt%) meets the values set by the European Biochar Certificate (EBC); where a minimum C content of 50 % allows to use a BC as a soil amendment (EBC 2019). Furthermore, Bayu et al(2017) stated that a high concentration of C in the BC favors the properties of the material to be used as a soil amendment since the C availability in the treated soil increases. Additionally, it is highlighted that during the gasification process, the N is transformed into water-soluble compounds, such as the ammonium nitrate (De la Rosa et al 2016), which benefits the fixation of microbial and vegetable N. This favors the biogeochemical cycle of N and reduces nitrous oxide emissions (N 2 O) through nitrification and denitrification (Wang et al 2019).…”
Section: Bc Physicochemical Characterizationmentioning
confidence: 99%
“…Similar results were reported by Díez and Pérez (2019) when characterized BCs derived from the gasification of different forest species (wood chips). Therefore, according to the properties of PL-BC and CH-BC, these BCs can be used as soil amendments, mainly acid ones (Bayu et al 2017). Concerning the CEC, there are alternatives to improve this property, among which it is highlighted the mixing with compost (Nsamba et al 2015).…”
Section: Bcs As Soil Amendmentsmentioning
confidence: 99%